Leadership Di Era Digital - Muh Naufal Mahfuuzhoh; Bintang Taufik Bisri; Hasna Risa; Mada Aditia Wardhana (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
Digital disruption demands leadership that can adapt to technological transformation, especially in learning organizations such as education, health, and government institutions. This study aims to map the concept of digital leadership, identify research gaps, and provide future research recommendations. The research method used is a Systematic Literature Review (SLR) and content analysis of 728 selected articles from 2016–2024 obtained via Crossref and Publish or Perish. The results indicate that digital leadership requires the integration of e-leadership skills, digital literacy, and social media-based communication. The study identifies gaps such as the lack of longitudinal studies, contextual analysis of specific platforms, and the absence of an integrative framework between digital literacy and communication patterns. The main contribution of this study is a conceptual framework for digital leadership and directions for future research in learning organizations. These findings are essential for designing adaptive strategies to face technological disruption systematically and sustainably.